MODIFIED EVALUATION OF INTELLECTUAL CAPITAL IN RUSSIAN CORPORATIONS BASED ON THE INCOME APPROACH: PERSPECTIVE VIEW - Manuylenko, Viktoriya; Ermakova, Galina (Revista Inclusiones, 2020)
The study contains modified strategic evaluation of intellectual human capital in corporations. The evaluation is based on the income approach and implies determination of relative degree of value added by human capital. It is based on simulation modeling and is arranged with special copyright software product, professional judgment of evaluation objects is considered. Practical application of the evaluation contributes to achievement of specific operational and strategic goals of corporations which integrate interests of different stakeholder groups, determines actual and potential interior courses for strategic development in a turbulent environment, and finally, gradually increases intellectual capital value. Promising tool for intellectual capital evaluation in corporations based on the income approach was applied as well as general scientific and special methods – i.e., inductive, deductive, analysis, including coefficient analysis, synthesis, grouping, system thinking, graphic analysis, comparative analysis, economics and statistics analysis, economics and mathematical analysis, extrapolation, expert estimates, methods of structural and logical schemes, copyright software, general MS EXCEL and special purpose EXCEL-VBA, etc